-2+11=13x-3-12x

Simple and best practice solution for -2+11=13x-3-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+11=13x-3-12x equation:


Simplifying
-2 + 11 = 13x + -3 + -12x

Combine like terms: -2 + 11 = 9
9 = 13x + -3 + -12x

Reorder the terms:
9 = -3 + 13x + -12x

Combine like terms: 13x + -12x = 1x
9 = -3 + 1x

Solving
9 = -3 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
9 + -1x = -3 + 1x + -1x

Combine like terms: 1x + -1x = 0
9 + -1x = -3 + 0
9 + -1x = -3

Add '-9' to each side of the equation.
9 + -9 + -1x = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = -3 + -9
-1x = -3 + -9

Combine like terms: -3 + -9 = -12
-1x = -12

Divide each side by '-1'.
x = 12

Simplifying
x = 12

See similar equations:

| y=35+-0.2018x | | y=35-0.2018(x) | | (6xy-3)(3xy+5)= | | 0.9y-0.4y=6.5 | | d-10=-16 | | 4(t-5)+6t=5(2t+4)-11 | | x=(-5i)(-6i) | | -1/7-3/2w=4/5 | | -3(3s-5)-15=-3(8s+1)-3 | | x=(5+7i)-(6-8i) | | x=(5+7i)(6-8i) | | -2/3-1/4v=-1/5 | | 160.03=2.72w+14.84 | | 12(2)+15(2)-9+5=-3(2)+5-9 | | 5X+2X-3Y=13-2 | | 1-2(3x-4)=5x-2(3x-5) | | 1/2=-1/2x-6/5 | | -7/2+6/7x=-8/3 | | -2(3s-5)-10=-3(5s+3)-5 | | .24(18)+0.04x=0.08(24+x) | | 2r^2-6r/r-3 | | 5w^2+7w=6 | | 2p+7=5-(11p+6) | | 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 | | 3x+2x+2=9 | | 7822-3008= |

Equations solver categories